New Hexactinellid Sponge Chaunoplectella megapora sp. nov. (Lyssacinosida: Leucopsacidae) from Clarion-Clipperton Fracture Zone, Eastern Pacific Ocean - Wang, Chunsheng; Zhang, Yuan; Lu, Bo; Wang, Dexiang (Zootaxa, 2018)
The new Hexactinellid sponge Chaunoplectella megapora sp. nov. reported in this study was collected from the COMRA contract area, the western part of Clarion-Clipperton Fracture Zone (CCFZ) in the eastern Pacific Ocean at a depth of 5258 m. This sponge’s extraordinary multiporous body with the presence of unique codonhexasters, sigmatocomes, toothed discohexasters and hemidiscohexasters, as well as stellate disocohexasters, characterizes it as a new species in the genus Chaunoplectella. This report presents the first record of family Leucopsacidae at this site in the eastern Pacific Ocean.